Collection Lags and the Optimal Inflation Tax : A Reconsideration - Tijerina, Jose (IMF Working Papers; Working Paper ;, 1993)
The observation that collection lags combine with inflation to erode fiscal revenues has long been a strong argument against seigniorage (Tanzi (1978)). However, with the exception of Dixit (1991), who used a general equilibrium model to reject this argument, the optimal tax literature has not analyzed how collection lags affect desired tax structures. In this paper, this issue is re-examined using an overlapping generations version of Dixit's model. It is shown that depending on the specification of the collection cost function and the size of government spending in GDP, collection lags may increase, leave unchanged, or reduce the desired rate of inflation.